Exploring Ultrafast Photoswitching Pathways in RbMnFe Prussian Blue Analogue. Issue 43 (15th August 2021) - Azzolina, Giovanni; Tokoro, Hiroko; Imoto, Kenta; Yoshikiyo, Marie; Ohkoshi, Shin‐ichi; Collet, Eric
Abstract: We study by femtosecond optical pump‐probe spectroscopy the photoinduced charge transfer (CT) in the RbMnFe Prussian blue analogue. Previous studies evidenced the local nature of the photoinduced Mn III Fe II → Mn II Fe III process, occurring within less than 1 ps. Here we show experimentally that two photoswitching pathways exist, depending on the excitation pump wavelength, which is confirmed by band structure calculations. Photoexcitation of α spins corresponds to the Mn(d‐d) band, which drives reverse Jahn–Teller distortion through the population of antibonding Mn‐N orbitals, and induces CT within ≈190 fs. The process launches coherent lattice torsion during the self‐trapping of the CT small‐polaron. Photoexcitation of β spins drives intervalence Fe→Mn CT towards non‐bonding states and results in a slower dynamic. Abstract : Time‐resolved optical spectroscopy combined to electronic band structure calculations revealed two photoinduced charge‐transfer pathways for RbMnFe Prussian blue analogue. Photoexcitation of α spins couples to reverse Jahn–Teller distortion that induces CT, while photoexcitation of β spins induces Fe→Mn CT, stabilized by a spin transition. Lattice torsion modes play an important role for accommodating local distortions and stabilizing CT.